PENGARUH PERSISTENSI LABA DAN LEVERAGE TERHADAP EARNING RESPONSE COEFFICIENT - Gurusinga, Jessica Jiley; Pinem, Dahlia Br (EQUITY, 2016)
This study is to conducted to examine the effect of variable earning persistence and leverage toward earning response coefficient. This study used 15 manufacturing companies belonging goodand food industry are listed in the Indonesia Stock Exchange in 2011-2013. The sampling technique used in this research was purposive sampling, based on criteria, there are 35 companies and tested with multiple regression analysis. The type of data used is secondary data obtained from www.idx.co.id and yahoo.finance.com and hypothesis test using t-statistic and f-statistic with significance level of 5%. These results indicate that the effect is not significant earnings persistence and leverage significant effect. The resulted of examinations can be used as basic information for investors before do the injections. Based on this study it can be delivered to the investor Indonesia Stock Exchange (BEI) to pay attention to other factors in response to the earnings announcement on the company's stock market analysis.